(untitled) (Bangladesh Journal of Child Health, 2018)
In every case of blood transfusion, so called proper donor screening is done every day. At the end of beautiful day, after reviewing lots of national and international guidelines and papers of blood transfusion, proved that blood donor screening methods & tests are not adequate & appropriate according to WHO. Lots of multi-transfused thalassemic & hemophiliac patients getting hepatitis B virus undoubtedly. Implementations of strict donor selection criteria and use of sensitive laboratory screening tests reduce the incidence of HBV transfusion. These courageous heartiest review may awake the decision makers thinking rethinking about HBV free blood transfusion service in Bangladesh. Bangladesh J Child Health 2017; VOL 41 (3) :181-188